Quizizz-Assisted Cognitive Diagnostic Assessment in Pancasila Education Learning in Elementary Schools - Reinita; Kaifiyatus Syahroh (Universitas Pendidikan Ganesha, 2024)
Lack of evaluation tools in learning that are appropriate to the needs and competencies of each student. This study aims to create a cognitive diagnostic assessment assisted by Quizizz in Pancasila education learning in grade IV of Elementary School. This study is a development research study using the ADDIE model. The method and instrument for data collection used a questionnaire. The data analysis technique used quantitative and qualitative analysis. The study results showed that the validation of the three validators (material, language and assessment) obtained a valid percentage and was worthy of being tested. Overall, the results of teacher practicality in the developed cognitive diagnostic assessment assisted by Quizizz reached 92.175% with a convenient category. The results of the cognitive diagnostic assessment's effectiveness obtained an N-Gain result of 0.61 with a moderate category. The study's conclusion shows that the cognitive diagnostic assessment assisted by Quizizz can be used in Pancasila education learning in grade IV of Elementary School. This study implies that it can motivate students to continue learning and focus more on the review process before the evaluation. This research implies that Quizizz-assisted cognitive diagnostic assessment in Pancasila education learning is suitable for use in learning.